Designing of Secure Hashing Algorithm 3 (SHA-3) in Bluespec System Verilog and Python - Vanamala, Manuraj; Jampani, Sarath Chandra; Sk, Noor Mahammad (2024 Second International Conference on Emerging Trends in Information Technology and Engineering (ICETITE), 2024)
The primary goal of this study is to implement Secure Hashing Algorithm 3 in hardware. The National Institute of Standards and Technology (NIST) created the cryptographic hash function SHA-3 to offer a high degree of security and cryp-tographic strength. Keccak Family Algorithms are the foundation upon which SHA-3 functions are built. Because Bluespec System Verilog provides a higher level of abstraction than other RTL languages, it is employed in this project's development. Python is used in the development of the SHA-3 software. Hardware systems using SHA-3 can withstand cryptographic attacks much better. SHA-3 can be used in embedded systems and Internet of Things devices to confirm the integrity of the bootloader code and firmware when the device is booting up. This ensures that only trusted and unaltered code is executed, guarding against malware and unauthorized access.